Hemidactylus frenatus (Sauria: Gekkonidae) en el noroeste de México. - Valdez-Villavicencio, Jorge Heriberto; Peralta-García, Anny (Instituto de Ecología, A.C., 2008)
New records of the introduced gecko Hemidactylus frenatus from northwestern México are provided. One of them represents the first record for the state of Sonora.